QUALITY OF LIFE, PHYSICAL ACTIVITY AND COGNITION IN THE ELDERLY POPULATION: A SYSTEMATIC REVIEW - Fabiano Nazar; Fabio Ricardo Hilgenberg Gomes; Valdomiro de Oliveira; Gislaine Cristina Vagetti (UNINGÁ Review, 2020)
This study reviewed the literature on "quality of life, physical activity and cognition in the elderly population". The search of the manuscripts was performed in seven databases and in the reference list of the selected articles. We included in the review the original studies, published between 2005 and 2017, which investigated the association or the relationship between quality of life (QL), physical activity (PA) and cognition, or had as an outcome any of these variables in older people. The search yielded 544 potentially relevant titles; 15 studies met the inclusion criteria and were reviewed. Four intervention studies were found, one prospective cohort study and eleven cross-sectional studies. Of the total number of studies, 87.5% involved elderly of both sexes. QL was largely related to the fact that they are physically active, and Cognition was associated to PA and good perception of QL. Education appeared in most studies as a sociodemographic data; only one study applied education as an intervention. The evidence on the impact of PA frequency and intensity on QL and Cognition aspects is still limited. Longitudinal and intervention studies are needed to better understand this dose/response relationship between PA, QL and cognition. The association between PA, QL and cognition is more complex than is usually exposed in the literature; moreover, it seems to involve more mediating variables.